Determination of 15 Rare Earth Elements in Phosphate Ores by Inductively Coupled Plasma-Mass Spectrometry with Atmospheric Pressure Closed Microwave Digestion - Nan ZHANG; Zhikang ZHENG; Jiasong WANG; Jiangping ZENG (Yankuang ceshi)
It takes a long time to treat ore samples by traditional alkali fusion and acid dissolution, and it is easy to cause environmental pollution. Microwave digestion directly releases energy to the sample with high efficiency, and volatile elements are retained in the digestion solution to prevent volatilization from causing deviation of results and environmental pollution. In this experiment, 0.2g of phosphate rock sample was taken and placed in a microwave digestion tank. 3mL hydrochloric acid, 3mL nitric acid, and 2mL hydrofluoric acid were added and then dissolved in the microwave digestion instrument. Then, 2mL of saturated boric acid solution was added for a further microwave digestion. After cooling, the sample was diluted in a 100mL volumetric flask with deionized water. Online addition of rhodium and rhenium as dual internal standards for inductively coupled plasma-mass spectrometry (ICP-MS) determination of rare earth elements in phosphate rock was performed. The relative standard deviation (RSD) of 15 rare earth elements was between 0.68% and 4.52%, the recovery was between 93.1% and 106.6%, and detection limit was between 0.003-0.029μg/g. Two phosphate ore samples were selected and compared with the mixed acid dissolution method. The relative standard deviation was −5.82%-5.99%.